Implikasi Infak Dalam Pembangunan Masjid - Ridho Robby Nugroho; Arief Nugroho; Hyldalia Arindra Pratama; Kiki Oktiyana; Lailatul Isti'ana; Putri Nabila Qawiah; Siti Saerah Ahmad Maulani; Tania Salsabela Surya Saputra; Ulfah Banatun; Nur Rofiq (SMA Trensains Muhammadiyah Sragen, 2024)
Infak is a voluntary social charity institution run by one person and the owner has the freedom to determine the type of assets and level of assets to be issued. Infak can be used to help ease the burdens of others and also increase devotion to God Almighty. Apart from that, donations can impact religious activities, for example helping fund the construction of a mosque. This research was carried out to learn more about donations' implications in mosque construction. This research uses a normative literature study method, namely by conducting literature research; with collection techniques through written sources. With this research, it is hoped that students will be able to pay more attention to the surrounding conditions that need help